(untitled) (CIPEEX, 2025)
Even with numerous advances in public health in Brazil, quality access for women is still a challenge, especially when they are homeless. Often, they do not have any type of information, such as information related to the health strategies offered. According to the Ministry of Health and the National Policy for Comprehensive Care for Women’s Health, all women have the right to quality care regarding family planning strategies, which is one of its operating principles. Thus, the objective of this production is to identify the main barriers that prevent homeless women from accessing family planning services. This study is an integrative literature review with searches for articles published in the last five years, using the descriptors: homeless women; family planning and health in the Virtual Health Library (BVS) and PubMed databases. From this review, it was seen that the lack of access of homeless women to family planning is a historical problem. Since centuries ago, women had no right to choose over their bodies. They were used only for reproductive purposes and for taking care of the home. Over the years, through an intense struggle, they have achieved some rights, which have been demanded throughout world history. There is still a long way to go, aiming not only at gender equality, but also at respect, especially for those living on the streets. They live in a situation of extreme abuse, in all areas. The need to create public policies that support this class and offer regulated support is observed and discussed in the productions, so that in the future the barriers to access to women’s health are not permanent.